Unusual presentation of bilateral tuberculous otomastoiditis with tuberculous spondylitis in a 14-year-old child: A case report - Reyhan E. Yunus; Ayu A. Sriyana (Radiology Case Reports, 2024)
Tuberculous otomastoiditis, a rare manifestation of tuberculosis in the head and neck region, poses diagnostic and therapeutic challenges due to its non-specific clinical features and potential debilitating complications. While typically arising from direct spread from adjacent organs, the coexistence of tuberculous otomastoiditis and cervical spondylitis is rarely reported. We present the case of a 14-year-old male with a 3-month history of painless bilateral ear discharge resistant to antibiotic therapy. The clinical and radiological findings raised suspicions of tuberculous otomastoiditis and spondylitis, which was later confirmed by histopathological examination despite negative microbiological cultures. This case underscores the significance of considering tuberculosis in conditions involving multiple organs, especially when persistent extensive damage is observed despite optimal initial treatments.